2023
DOI: 10.1002/csc2.20927
|View full text |Cite
|
Sign up to set email alerts
|

Inbred phenotypic data and non‐additive effects can enhance genomic prediction models for hybrid grain sorghum

Abstract: Implementation of genomic prediction can bolster rates of genetic gain in sorghum improvement and permit more efficient allocation of resources within hybrid breeding programs. In the present study, alternative genomic prediction models were compared to assess the potential benefits of including inbred phenotypic records, dominance effects, and genotype-by-environment (G×E) interactions in predicting hybrid grain sorghum performance. Comparisons were made in a set of 395 hybrid combinations derived from 92 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…The prediction accuracies for days to mid-anthesis and grain yield ( Figure 4 ) are like those reported in other studies in sorghum [ 5 , 15 , 16 , 20 , 21 , 22 , 23 ]. However, the prediction accuracies for plant height are lower than in previous studies, much like what was observed by Winans et al [ 5 ] and Sapkota et al [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prediction accuracies for days to mid-anthesis and grain yield ( Figure 4 ) are like those reported in other studies in sorghum [ 5 , 15 , 16 , 20 , 21 , 22 , 23 ]. However, the prediction accuracies for plant height are lower than in previous studies, much like what was observed by Winans et al [ 5 ] and Sapkota et al [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…From observation, there is a large amount of variation in plant height, and it is likely that a few of the families are segregating for major dwarfing genes. Studies reporting high prediction accuracy for plant height had lines subject to more intense selection pressure, and it is likely that large-effect genes that control height were fixed [ 16 , 21 , 23 ], whereas studies with large variation in height, exotic germplasms, and minimal selection reported lower prediction accuracies [ 5 , 22 ]. Within this study, the GBLUP approach is limited in its ability to capture large single gene effects due to the distributed weight of effects across the genome [ 11 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Crozier et al. (2023) demonstrated that genomic prediction of hybrid performance can be improved by adding inbred data into the training data. This may be further useful if predicted inbred phenotypes could be used to improve the prediction of hybrids as this would save resources by reducing the need of inbred phenotyping.…”
Section: Resultsmentioning
confidence: 99%
“…Although the observations made herein regarding training set size were demonstrated in inbred lines, it is conceivable that similar trends would apply to sorghum hybrids, although studies are needed to support this claim. Additionally, Crozier et al (2023) demonstrated that genomic prediction of hybrid performance can be improved by adding inbred data into the training data. This may be further useful if predicted inbred phenotypes could be used to improve the prediction of hybrids as this would save resources by reducing the need of inbred phenotyping.…”
Section: Crop Sciencementioning
confidence: 99%
“…However, the broad application of GS in sorghum breeding programs might be hindered by G × E in certain regions (Hunt et al., 2018). To account for multiple environmental factors, ongoing research on genomic prediction in sorghum is exploring the incorporation of G × E into prediction models (Crozier et al., 2023; Fonseca et al., 2021). While G × E effects seem to positively impact the prediction accuracy of critical sorghum traits (Crozier et al., 2023), the incongruous outcomes from G × E suggest that factors beyond environment correlations drive genomic predictions in sorghum hybrids for grain production (Fonseca et al., 2021).…”
Section: Introductionmentioning
confidence: 99%